Petrology, age, and tectonic setting of The Wolves Pluton:: implications for Appalachian terranes in the western Bay of Fundy region - Wolczanski, Heather; Barr, Sandra; Miller, Brent (Atlantic Geology, 2007)
ABSTRACT The islands known as The Wolves are located in the Bay of Fundy, approximately 10 km offshore from mainland southwestern New Brunswick. They are underlain by monzodiorite, gradational to diorite, quartz diorite, and quartz monzodiorite, and minor units of tonalite and quartz monzonite, herein termed collectively The Wolves Pluton. Finer grained dioritic xenoliths are abundant in all the units. Rare syenite dykes and scattered mafic dykes intrude the pluton. Samples from the monzodiorite unit have silica concentrations ranging from 47.6% to 59.6% (average 54.5%), whereas tonalite samples have higher SiO2 from 65.4% to 73.3% (average 69.6%) and two quartz monzonite samples have about 69% SiO2. Although finer grained, the xenoliths are generally similar in mineralogy and chemical composition (49.2–54.7% SiO2) to the dioritic part of the monzodiorite unit. Based on continuity and similarity of chemical trends and patterns, the monzodiorite, tonalite, and quartz monzonite, as well as the dioritic xenoliths, are interpreted to be co-magmatic. They constitute a calc-alkalic, I-type granitoid suite that likely formed in a subduction zone. A sample of monzodiorite from East Wolf Island yielded an Early Silurian U-Pb age of 436.4 ± 1.2 Ma, showing that The Wolves Pluton is not related to the Late Neoproterozoic to Early Cambrian plutonic rocks of the Caledonia, Brookville, and New River terranes, or of Grand Manan Island. They are older than Late Silurian-Devonian plutons of the Coastal Maine Magmatic Province. The best match in age is with Lower Silurian volcanic and granitic units of the Kingston terrane, although the rocks of The Wolves Pluton differ petrologically from the mainly fine-grained granite typically exposed in the Kingston terrane. Nevertheless, the similarity in age and inferred tectonic setting, as well as their similar positive epsilon Nd signatures, suggest that The Wolves Pluton might represent a deeper part of the Kingston volcanic arc. If so, the location of The Wolves Pluton apparently necessitates sinistral offset of the Kingston terrane to the southeast.